T1N6_22 positively regulates Botrytis cinerea resistance but negatively regulates Pseudomonas syringae pv. tomato DC3000 resistance in Arabidopsis thaliana - Qiao-yun Weng; Jin-hui Song; Ya-ting Zhao; Xu Zheng; Cong-cong Huang; Guan-yu Wang; Jing Zhang; Ji-hong Xing; Jin-gao Dong (Biotechnology & Biotechnological Equipment, 2017)
T1N6_22, a short-chain dehydrogenase/reductase family protein, was identified as a positive regulator in Arabidopsis thaliana resistance against Botrytis cinerea and Alternaria brassicae in our preliminary study. In this study, we found that the expression levels of the T1N6_22 gene were induced and up-regulated in A. thaliana ecotype Columbia (Col-0) after B. cinerea and Pseudomonas syringae pv. tomato DC3000 inoculation. Compared with the Col-0 and t1n6_22/T1N6_22 plants, the expression of PAL, PR4, PPO, SOD and CAT genes were down-regulated in the t1n6_22 plants. In Col-0 plants treated with salicylic acid (SA) and the SA analogue benzo(1,2,3)thiadiazole-7-carbothioic acid S-methyl ester (BTH), the expression levels of T1N6_22 were significantly enhanced, whereas the expression levels of T1N6_22 were reduced by jasmonic acid treatment. Meanwhile, the t1n6_22 mutant exhibited enhanced resistance, whereas the wild-type Col-0 and complemented plants (t1n6_22/T1N6_22) showed susceptibility to Pst DC3000. After inoculation with B. cinerea and Pst DC3000, the expression levels of defence-related genes PR1, PR3, PR5, NPR1 and PDF1.2 in t1n6_22 were significantly different from those in Col-0 and t1n6_22/T1N6_22 plants. Taken together, the T1N6_22 gene played a negative role in Arabidopsis resistance to Pst DC3000. The T1N6_22 gene may be involved in the regulation of salicylic acid and jasmonic-acid–signalling pathways to affect the resistance of Arabidopsis to B. cinerea and Pst DC3000.